The applicability of the apportionment of Damages Act 34 of 1956 to contractual claims with emphasis on the development of apportionment laws in South Africa and similar foreign jurisdictions - Cornelius, Steve J. (University of Pretoria, 2013)
Dissertation (LLM)--University of Pretoria, 2012.